OBSERVATIONS ON THE MARINE PRAWN FISHERY BY SHORE SEINE AT KAKINADA - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
Prawns are fished all along the Andhra coast throughout the year inappreciable quantities. With annual landings estimated at 10,675 tonnes,(CMFRI 1976) prawns form an important fishery and contribute to about 7%of the marine fish production of the state. Despite their commercial importanceas an export commodity, practically nothing is known about the fishery andbiology of the component species of the region which is a prerequisite for arational exploitation of the resources. The present account deals with the datacollected during May 1966 to December 1971 at Kakinada, an important fishingcentre of the Andhra coast and attempts to describe briefly the prawn fisheryby the shore-seines in the inshore waters with notes on some aspects of thebiology of a few commercially important species.